Acceptability and prescribing adherence to revised antiemetic guidelines in paediatric patients receiving chemotherapy. Issue 5 (22nd April 2012) - Richardson, N; Ferguson, J; Cooper, G; Kinnear, M; Brinton, L; Neslen, E
Abstract : Objective: To assess adherence to and acceptability of revised antiemetic prescribing guidelines implemented 20091 and evaluation of use of the patient-specific antiemetic record. Methods: Case notes, prescription and administration charts were reviewed retrospectively for 20 patients receiving chemotherapy during April 2011. Prescribing of chemotherapy and antiemetics over the previous 12 months was recorded and adherence to guidelines assessed. Recently implemented patient sickness diary cards completed by patients/carers on each cycle of chemotherapy were evaluated. Prescribers' views and awareness of the guidelines were gathered from a specifically designed self-administered questionnaire. Outcomes from the study were presented at a multidisciplinary meeting where changes in practice were agreed. Results: Of the 20 patients (11 oncology; 9 haematology), 13 were male and ranged from 6 months to 19 years old. Five patients had received chemotherapy for longer than 12 months. Prescribing adhered to the guidelines greater than 70% of the time in eight patients, between 30–70% of the time in 10 patients and less than 30% of the time in two patients. Non-adherence trends were: unclear documentation of patients receiving prechemotherapy antiemetics, ondansetron continued longer than 24 h postchemotherapy to prevent acute nausea and vomiting, metoclopramide started concomitantly with ondansetron for prevention of delayed nausea and vomiting and lorazepam not being administered immediately post an acute emetic episode. Non-adherence was justified when there was a previous adverse reaction to an antiemetic or when emesis continued despite appropriate management and/or confounding circumstances such as parenteral nutrition. Omissions from the guidelines were use of aprepitant in teenagers receiving cisplatin-based regimens, emetogenic risk of clofarabine and intrathecal cytarabine and guidance on evaluating emetogenic risk for investigational medicinal products such as chimeric 14.18/CHO monoclonal antibody (antiGD2). Five patients returned completed Patient Sickness Diary Cards. Excluding one patient with low-grade glioma and pre-existing vomiting prior to chemotherapy who experienced 13 vomits over a 5 day reporting period, only three vomits were noted over a total of 36 days reported but 22 patient days (61%) were recorded as nauseated. 17 out of 35 (49%) prescriber questionnaires were returned. Prescribers reported awareness of the guidelines and considered them helpful. The patient specific antiemetic record was not used, and there was multidisciplinary agreement that working practices be reviewed to facilitate accessibility. Conclusion: The revised guidelines are mostly adhered to and the results have informed where adjustments and additional information are required. The patient diary card and the patient specific antiemetic record were considered useful in the individualisation of treatment and are to be integrated into working practices and used for continuous quality monitoring.